Smart home irrigation: A solar-powered Wi-Fi-based automated drip system with real-time soil moisture sensing - Dominic Olango Cagadas; Cran Leigh Mae Adis Salamanca (Innovation in Engineering, 2026)
Manual irrigation in home gardening often causes inconsistent watering, unnecessary labor, and inefficient water use. This study developed and evaluated a solar-powered, Wi-Fi-based automated drip irrigation system with real-time soil moisture sensing for small-scale home gardens. The prototype integrated an ESP32 microcontroller, capacitive soil moisture sensors, pH sensor, float sensors, solenoid valves, DC pumps, a 150-W solar panel, a 12.8-V 100-Ah battery, and an Android-based mobile application. Four planting plots were used to test automated irrigation, soil moisture monitoring, water pH monitoring, tank-level detection, drainage monitoring, and mobile-based control. System performance was observed through 15-day plant monitoring and 5-day data logging. Results showed that the system supplied water only when soil moisture dropped below the set threshold and avoided unnecessary pump activation. Evaluations by 20 faculty members, IT experts, agriculturists, and farmers yielded excellent ratings for functionality (4.81), performance (4.74), and usability (4.89), with an overall mean of 4.81. The study demonstrates a low-cost, renewable-energy-based, mobile-controlled irrigation solution suitable for household gardening.